Structural characterization and corepressor binding of the Escherichia coli purine repressor. - Choi, K Y (1992)
The Escherichia coli purine repressor, PurR, binds to a 16-bp operator sequence and coregulates the genes for de novo synthesis of purine and pyrimidine nucleotides, formation of a one-carbon unit for biosynthesis, and deamination of cytosine. We have characterized the purified repressor. Chemical cross-linking indicates that PurR is dimeric. Each subunit has an N-terminal domain of 52 amino acids for DNA binding and a C-terminal 289-residue domain for corepressor binding. Each domain was isolated after cleavage by trypsin. Sites for dimer formation are present within the corepressor binding domain. The corepressors hypoxanthine and guanine bind cooperatively to distinct sites in each subunit. Competition experiments indicate that binding of one purine abolishes cooperativity and decreases the affinity and the binding of the second corepressor. Binding of each corepressor results in a conformation change in the corepressor binding domain that was detected by intrinsic fluorescence of three tryptophan residues. These experiments characterize PurR as a complex allosteric regulatory protein.